2021
DOI: 10.1038/s41398-021-01445-0
|View full text |Cite
|
Sign up to set email alerts
|

Personalized machine learning of depressed mood using wearables

Abstract: Depression is a multifaceted illness with large interindividual variability in clinical response to treatment. In the era of digital medicine and precision therapeutics, new personalized treatment approaches are warranted for depression. Here, we use a combination of longitudinal ecological momentary assessments of depression, neurocognitive sampling synchronized with electroencephalography, and lifestyle data from wearables to generate individualized predictions of depressed mood over a 1-month time period. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 91 publications
2
84
3
1
Order By: Relevance
“…Ensemble learning [142,143] Recommendation systems and prediction of loneliness levels Improves the generalization capacity of the model and makes predictions using data-fusion techniques for multiple data sources…”
Section: Performs Well With the Categorical Datamentioning
confidence: 99%
“…Ensemble learning [142,143] Recommendation systems and prediction of loneliness levels Improves the generalization capacity of the model and makes predictions using data-fusion techniques for multiple data sources…”
Section: Performs Well With the Categorical Datamentioning
confidence: 99%
“…Wearable device data equipped with ML algorithms are helpful for extracting the highly personalized nature of psychological conditions such as depression and mood swings. A recent study on 14 young people using EEG data, neurocognitive assessments, and lifestyle data from wearable devices revealed that each person had distinct depression determinants [ 90 ]. Hence, highly personalized diagnoses and treatments are required.…”
Section: Wearables As Digital Diagnosticsmentioning
confidence: 99%
“…In addition to COVID-19 infection monitoring, wearables have shown to disrupt numerous healthcare domains, including cardiology [5], gait analysis [6], sleep quality [7], clinical trials during cancer treatment [8], stress management [9], and emotion/depression [10], just to name a few. In addition to healthcare, wearables have also seen applications in smart vehicles [11], pedestrian tracking [12], gaming [13] and extended reality [14], smart homes and robots [15], construction safety [16], and Industry 4.0 applications [17].…”
Section: Introductionmentioning
confidence: 99%